2014
DOI: 10.1177/0954410014524182
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control for far-distance rapid cooperative rendezvous

Abstract: This study investigated the far-distance cooperative rendezvous problem for two spacecrafts. The orbital dynamics equations were represented based on the orbital elements with an improved vernal equinox and were normalized. Pontryagin's extremum principle was introduced into the dynamics equations and the co-state equations were obtained. A performance evaluation function was created by particle swarm optimization algorithm based on simulated annealing. The convergent co-state initial vector was obtained using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…When the difference between the initial mass of two spacecraft is too large, a cooperative rendezvous will degenerate to an active–passive rendezvous and fuel consumption will automatically centralize to the lighter one. 4 In order to make sure that fuel consumption will be evenly burdened by two spacecraft, the standard deviation of fuel consumption of two spacecraft, noted as Δmsd is introduced. Objective function is revised as follows where Δm1 and Δm2 are fuel consumption of two spacecraft and λ is a coefficient.…”
Section: Problem Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…When the difference between the initial mass of two spacecraft is too large, a cooperative rendezvous will degenerate to an active–passive rendezvous and fuel consumption will automatically centralize to the lighter one. 4 In order to make sure that fuel consumption will be evenly burdened by two spacecraft, the standard deviation of fuel consumption of two spacecraft, noted as Δmsd is introduced. Objective function is revised as follows where Δm1 and Δm2 are fuel consumption of two spacecraft and λ is a coefficient.…”
Section: Problem Formulationmentioning
confidence: 99%
“…Some former studies gave fuel-optimal results of cooperative rendezvous between two spacecraft under continuous thrust. [4][5][6][7] Continuous thrust is more appropriate to fardistance orbit maneuver because it has been shown that far-distance orbit maneuver under high continuous thrust is less time consuming than impulse thrust. [8][9][10] However, continuous thrust has not been adopted in practical space missions yet owing to the limitation of engine technology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By adopting a separation target function and constraints method for the constraint optimization problem, the original problem is converted as follows: (17) where i points to the i-th particle, fitness(i) corresponds to the target function value sought, and voilation(i) corresponds to the problem constraint, jointly constructed by all the constraints, being sought; this value reflects the degree of closeness to the constraint boundary of particle i. Together, these two functions are the particle fitness functions.…”
Section: Establishment and Application Of The Double Fitness Functionmentioning
confidence: 99%
“…Therefore, the control process for spacecraft cooperative rendezvous has begun to garner more research attention. Past research on spacecraft cooperative rendezvous was primarily based on a scenario in which two spacecraft had equivalent masses [8,10,11,15,17]. In actual space operation, however, there are usually differences in the masses of the two spacecraft; at times, the differences can be relatively large.…”
Section: Introductionmentioning
confidence: 99%